Do job positions matter in emotional labor and in its relationship with job performance? - Ma, S.; Silva, M. G.; Trigo, V.; Callan, V. (Proceedings of the 11th European Conference on Management Leadership and Governance (ECMLG 2015), 2015)
A central focus of emotional labor research is on the frontline service workers and empirical research on managers has so far been rare (Humphrey 2012). Moreover, only limited research has examined the impact of emotional labor on job performance (Duke et al. 2009) and such paucity is aggravated if we consider samples from China. Considering these gaps in the literature, this study has three research questions. First, do employees at different hierarchical positions report different levels of emotional intelligence or does emotional intelligence increase as the job position increases? Second, do employees at different hierarchical positions report different levels of emotional labour or does emotional labour increase as the job position increases? Third, do levels of emotional labour predict levels of job performance across different positions in organizations? We address the research questions with a sample of 245 managerial professionals from business organizations in mainland China. Significant differences were found on emotional intelligence between those in senior positions (i.e., director or above) and ordinary employees. In addition, the results show that among ordinary employees, emotional intelligence and emotional labor are important predictors of job performance. Moreover, emotional labor has a moderating effect in the association between emotional intelligence and job performance, such that high levels of emotional intelligence were more likely to be associated with high levels of job performance when the demand of emotional labor increased. The relationship does not hold true for the managerial positions in our sample. This study suggests that the interaction effect between emotional intelligence and emotional labor does not hold equally true for employees in different positions.